Tectonic Setting and Evolution of the Grenville Orogen: An Assessment of Progress Over the Last 40 Years - Rivers, Toby (Geoscience Canada, 2015)
The Grenville Province is known for its high grade of metamorphism, complex ductile gneissic structure, and polyphase reworking, features indicative of residence in the deep crust (orogenic infrastructure) that hamper recognition of protoliths and original relationships and render tectonic interpretations especially challenging. This paper charts the evolving understanding from the ‘Grenville Problem’ of the 1950s before the plate tectonic paradigm, through a speculative quasiplate tectonic stage in the 1970s that effectively proved to be a dead end, and the first constrained plate tectonic models for pre-Grenvillian Laurentia in the 1980s, to the recent LHO (large hot orogen) and collapsed LHO models for the Grenville Orogen itself. The collapsed LHO model is based on the finding that significant amounts of the superstructure (upper orogenic crust) are preserved, and that the present crustal architecture can be explained by tectonic juxtaposition of infrastructure and superstructure in a late extensional event associated with crustal-scale collapse of a high-strain channel under an orogenic plateau. Conceptual breakthroughs and critical datasets assembled in the period 1980–2000 that were influential in guiding tectonic thinking are discussed and it is argued that present understanding was contingent on the results of 2-D numerical forward modelling of orogenesis, in particular the LHO experiments and the more recent models of orogenic collapse. As a result, for the first time a conceptual plate tectonic model for the convergence and collapse stages of the Grenville Orogen based on empirical field data (the inverse model) is broadly supported by numerical forward-modelling experiments constrained by physically plausible processes in a LHO – and both are available for future testing and refinement. Moreover, they may also have application to other enigmatic high-grade Proterozoic orogens that have resisted simple incorporation within the plate tectonic narrative.